STUDY OF THE PHYSICO-CHEMICAL PROPERTIES OF SACCHARINE SORGHUM MOLASSES (SORGHUM BICOLOR L. MOENCH) (Fiep Bulletin - online, 2012)
Due to the population growth not to be accompanied by the increase of the arable areas, seeks be cultivated that adapt better to certain areas and this way as the sorghum is a cereal of short maturation period whose culture is from high adaptability to the areas of low precipitations of rains, adverse soils and of great climatic varieties, such as the semi-arid Northeast, this study aimed to characterize the physico-chemical byproduct of sorghum (sorghum bicolor L. Moench) variety 467-4-2 IPA in the form of molasses. The molasses was obtained from the juice of sorghum stem and showed humidity content 15.4%, ashes 11.1%, with pH of 5.3, free acidity of 165 mEq / kg, hydroxymethylfurfural 0.6 mg/100g, diastasic activity equivalent to 13.9 in Table GOTHE, soluble solids 81g/100g and insoluble solids 0.45. The molasses was within the norms proposed by the legislation, except the ashes content, pH and acidity.
Keywords: sorghum; molasses; physicochemical characterization.